DERMOID AND EPIDERMOID CYSTS OF THE MAXILLOFACIAL AREA AND THE NECK AMONG CHILDREN - P.I. Tkachenko; I.I. Starchenko; S.O. Bilokon; Y.V. Popelo; N.P. Bilokon; V.V. Yarkovy (Український стоматологічний альманах, 2020)
It is generally accepted that dermoid and epidermoid cysts are the result of malformation of the ectoderm. The asymptomatic course, absence of pathognomonic symptoms and similarity of clinical manifestations at separate stages of growth, despite nosological form and place of occurrence, give this pathology of particular relevance in the practice of pediatric maxillofacial surgery.